Postimperial Englishness in the contemporary white canon - Dodson, E (2017)
Building upon ‘contrapuntal’ readings of canonical fiction by white English writers, this thesis conducts a postcolonial analysis of major contemporary English novelists who are not commonly associated with issues of race, empire, and decolonisation. The three main case studies are Alan Hollinghurst, Graham Swift, and Julian Barnes, but I also discuss a range of other prominent novelists including Ian McEwan, Hilary Mantel, and J.G. Ballard. Each chapter begins by challenging the dominant interpretative frameworks – Hollinghurst, sexuality; Swift, WWII; Barnes, postmodernism – within which each author is typically situated. The extended postcolonial readings that follow disrupt the critical separation of ‘postcolonial’ from ‘English’ contemporary fiction. These categories have led to ‘a consensual and still prevalent “parochiality” in terms of reading habits’, which I interpret as the refusal or inability to read for race, empire, and decolonisation where they are not expected – that is, in a Hollinghurst rather than a Rushdie – a division that seems to be conducted on biographical if not also racial criteria. The overall argument of this thesis is that the contemporary canon of white English novelists – often separated or shielded from postcolonial scrutiny – can be redefined as postimperial. By this I mean that they are engaged in the critical examination of England and Englishness after empire, with a particular emphasis upon issues of sexuality, militarism, and masculinity. Alan Hollinghurst, Graham Swift, and Julian Barnes are much more historically, geographically, and politically aware and engaged as writers than we have tended to imagine them as being. They write in response to the conditions of post-war and postimperial Britain, as well as in dialogue with both imperial writing and postcolonial writing. In doing so, and whilst addressing a range of other concerns and harnessing a number of different approaches, their fiction makes an important contribution to the registering and remaking of postimperial Englishness.